Renal Histopathologic Findings Associated With Severity of Clinical Acute Kidney Injury. (May 2018) - Kudose, Satoru; Hoshi, Masato; Jain, Sanjay; Gaut, Joseph P.
Abstract : Acute kidney injury (AKI) is a significant cause of morbidity and mortality. Acute tubular injury is considered to be the early pathologic manifestation of AKI, however, the underlying pathology is complex, lacks standards for interpretation, and its relationship with AKI often is unclear or inconsistent. To clarify clinicopathologic correlations in AKI, we evaluated 32 histologic findings in 100 kidney biopsies from patients with AKI as a training set to correlate pathologic findings with clinical AKI grades. Kidney Injury Molecule-1 quantitative immunohistochemistry was performed to confirm tubular injury. A separate cohort of 50 biopsies were evaluated blinded to clinical information to validate the findings. Pathologic tubular injury correlated best with Kidney Disease Improving Global Outcomes criteria. Tubular epithelial simplification, tubular epithelial mitosis, and cell sloughing correlated well with clinically severe AKI and were used to construct a tubular injury classification scheme with sensitivity of 0.93 (0.85, 1), specificity of 0.95 (0.83, 1), and area under the receiver-operating characteristic curve of 0.98 (0.98, 1) for grades 2 to 3 AKI. Predictive ability of the model did not improve when Kidney Injury Molecule-1 immunostaining results were added. The results show a strong correlation between pathologic tubular injury and modern clinical definitions of AKI. The proposed classification scheme may aid in development of more precise and clinically meaningful interpretations of pathologic tubular injury in native kidney biopsies and provides simple pathologic criteria without special studies that can easily be adopted globally. Abstract : Supplemental Digital Content is available in the text.